THE STRATEGY OF KNOWLEDGE TRANSFER IN THE REHABILITATION PROJECT OF IMMANUEL CHURCH (BLEDUK), SEMARANG CITY - Ruliana Febrianty; Mochamad Agung Wibowo; Jati Utomo Dwi Hatmoko (International Journal on Livable Space, 2025)
The knowledge transfer plays a vital role in maintaining the quality of construction projects, especially in the rehabilitation of heritage buildings, which demand a contextual expertise and a deep understanding of historical values. Aims: This study aims to explore and analyze the implementation of knowledge transfer strategies by construction companies in the historical building conservation projects. Methodology and results: Employing a qualitative approach, data were collected through in-depth interviews, field observations, and document analysis of selected rehabilitation projects. The findings indicate that knowledge transfer in such projects is predominantly informal and relies on individual experience, interpersonal networks, and intergenerational communication. Tacit knowledge, including traditional conservation techniques and assessment of aged materials, remains undocumented and is not incorporated into formal knowledge management systems. Conslusion, significant, and impact of study:  The identification of effective strategies includes experience-based mentorship, cross-generational collaboration, team-incentives, and documented digitial-tools. The study recommends the development of adaptive and participatory knowledge management systems to enhance the sustainability of conservation practices and preserve historical values across generations.